Ferric quinate (QPLEX) inhibits the interaction of major outer membrane protein (MOMP) with the Lewis b (Leb) antigen and limits Campylobacter colonization in broilers - Okoye, Jennifer C.; Holland, Alexandria; Pitoulias, Matthaios; Paschalis, Vasileios; Piddubnyi, Artem; Dufailu, Osman A.; Borén, Thomas; Oldfield, Neil J.; Mahdavi, Jafar; Soultanas, Panos (Frontiers in Microbiology, 2023)
Campylobacter jejuni colonises hosts by interacting with Blood Group Antigens (BgAgs) on the surface of gastrointestinal epithelia. Genetic variations in BgAg expression affects host susceptibility to C. jejuni. Here, we show that the essential Major Outer Membrane Protein (MOMP) of C. jejuni NCTC11168 binds to the Lewis b (Leb) antigen on the gastrointestinal epithelia of host tissues and this interaction can be competitively inhibited by Ferric Quinate (QPLEX), a ferric chelate structurally similar to bacterial siderophores. We provide evidence that QPLEX competitively inhibits the MOMP-Leb interaction. Furthermore, we demonstrate that QPLEX can be used as a feed additive in broiler farming to significantly reduce C. jejuni colonization. Our results indicate that QPLEX can be a viable alternative to the preventative use of antibiotics in broiler farming to combat C. jejuni infections.